Characterization of Zn0. 95Mn0.05O synthesized by polymeric precursors - Gama, Lucianna; Ribeiro, Maria Aparecida; Santos, Adyllis Marcelo Cunha; Kiminami, Ruth Herta Goldschmidt Aliaga; De Melo Costa, Ana Cristina Figueiredo [UNESP]; Bernardi, Maria Inês Basso (My University, 2008)
This paper discusses the preparation and characterization of Zn 0.95Mn0.05O phase obtained by the polymeric precursor method for DMS applications. The as-obtained powders were calcined between 500 to 800°C and characterized by XRD, SEM and BET. The XRD analysis of the powder showed a crystalline material containing second phase. The crystallite sizes ranged from 20 to 51 nm. The micrographs showed that the powders consisted of soft and homogeneous agglomerations. The nitrogen adsorption/desorption curves of the Zn0.95Mn0.05O phases were type II curves, which is characteristic of mesoporous materials.
Keywords: DMS; Pechini Method; ZnO-Mn; Nitrogen adsorption; Pechini method; Polymeric precursor methods; Polymeric precursors; Second phase; Type II; XRD; XRD analysis; Calcination; Ceramic materials; Crystalline materials; Manganese; Mesoporous materials; Powders; Zinc; Zinc oxide; Polymers